2001
DOI: 10.1046/j.1365-2672.2001.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a quantitative risk assessment for BSE in sewage sludge

Abstract: Aims:The aim is to determine the risk of transmission of BSE to humans and cattle through the application of sewage sludge to agricultural land. Methods and Results: A quantitative risk assessment based on the Source±Pathway±Receptor approach is developed. Central to the model is the estimation of the arithmetic mean concentration of BSE agent in sewage sludge. The main sources of uncertainty in the risk assessment are the degree to which sewage sludge treatment destroys BSE agent, whether there is a threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 12 publications
(34 reference statements)
2
65
0
Order By: Relevance
“…The authors concluded that, although they recognized the potential for risk of BSE infection via sludge-derived fertilizer, scientific data in support of the hypothesis was insufficient. Gale and Stanfield [1] conducted quantitative evaluations of the risk of BSE infection in humans and cattle via sludge-derived fertilizer route in the United Kingdom. They estimated that the BSE infectious value ingested by one head of cattle per year was 7.07 × 10 -4 bovine oral ID 50 , when the sludge from 700,000 cattle, including 3,780 infected cattle was applied to pastureland per year and implied that 49.5 cattle per year could become infected by BSE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that, although they recognized the potential for risk of BSE infection via sludge-derived fertilizer, scientific data in support of the hypothesis was insufficient. Gale and Stanfield [1] conducted quantitative evaluations of the risk of BSE infection in humans and cattle via sludge-derived fertilizer route in the United Kingdom. They estimated that the BSE infectious value ingested by one head of cattle per year was 7.07 × 10 -4 bovine oral ID 50 , when the sludge from 700,000 cattle, including 3,780 infected cattle was applied to pastureland per year and implied that 49.5 cattle per year could become infected by BSE.…”
Section: Discussionmentioning
confidence: 99%
“…In the report on slaughterhouse sewage contamination in the United Kingdom, Gale and Stanfield [1] estimated that the risk posed by SRM contamination of sewage by tissue derived from stunning, pithing and splitting passing through 4-mm mesh filters installed along sewage drains was likely to be a maximum of 1% of the total SRM from one infected animal. While many slaughterhouses in Japan have removed spinal cord before splitting or installed filters into the drains with mesh sizes of 4 mm or less, the removal efficiency of these measures has not yet been clearly demonstrated.…”
Section: Possibility Of Srm Contamination Of Sewage At Slaughterhousesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogens are a result of normal, human metabolic wastes as well as additional loading from medical effluents (Arthurson, 2008;Deblonde et al, 2011;Lewis et al, 2002;Mathney, 2011;Reilly, 2001;Straub et al, 1993;USEPA, 2009;Verlicchi et al, 2010). There are fewer than two dozen pathogens (e.g., fecal coliforms, Salmonella, enteric viruses, and parasites) monitored in sewage sludge (Mathney, 2011;NASNRC, 2002;Reilly, 2001;Snyder, 2005;USEPA, , 2002bUSEPA, , 2003, and many dangerous pathogens (e.g., prions) are neither affected by sewage treatment nor detected by standard analytical methods (Gale & Stanield, 2001;NASNRC, 2002;Peterson et al, 2008b;Saunders et al, 2008;Smith et al, 2011;Snyder, 2005).…”
Section: Pathogensmentioning
confidence: 99%
“…68 The investigation included assessment of BSE, foot-and-mouth disease, African swine fever, and classical swine fever by use of a quantitative MRA developed for assessment of BSE in sewage sludge. 39,73 It was concluded that the important factors governing risk were sources of composted animal parts, the efficiency of composting, and the decay and dilution in soil when compost was spread on pasture. The net pathogen destruction was heavily influenced by the degree of bypass, which is the compost that does not reach critical temperature because of its location in the pile.…”
Section: Microbial Risks Associated With Composting Of Animal Carcassesmentioning
confidence: 99%